Does it pay to be productive? The case of age groups - Alessandra Cataldi; Stephan Kampelmann; Francois Rycx (Institute for the Study of Labor (IZA), 2011)
Using longitudinal matched employer-employee data for the period 1999-2006, we investigate the relationship between age, wage and productivity in the Belgian private sector. More precisely, we examine how changes in the proportions of young (16-29 years), middle-aged (30-49 years) and older (more than 49 years) workers affect the productivity of firms and test for the presence of productivity-wage gaps. Results (robust to various potential econometric issues, including unobserved firm heterogeneity, endogeneity and state dependence) suggest that workers older than 49 are significantly less productive than prime age and young workers. In contrast, the productivity of middle-age workers is not found to be significantly different compared to young workers. Findings further indicate that average hourly wages within firms increase significantly and monotonically with age. Overall, this leads to the conclusion that young workers are paid below their marginal productivity while older workers appear to be overpaid and lends empirical support to theories of deferred compensation over the life-cycle (Lazear, 1979).
urn:nbn:de:101:1-201109286318
Keywords: J14; J24; J31; 330; wages; productivity; aging; matched panel data; Altersgruppe; Ältere Arbeitskräfte; Arbeitsproduktivität; Lohn; Schätzung; Belgien